Green's formula and theorems on complete collection of isomorphisms for general elliptic boundary value problems for Douglis-Nirenberg systems - Roitberg, Ya.; Roitberg, I. (Нелинейные граничные задачи, 1999)
This work has been partially supported by Grant INTAS-94-2187.